حدّ الفنّ المقامي الأندلسي وعناصر السّرد فيه - راشد, ذياب; داؤد, جمانة إبراهيم (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
استوى عود الفنّ المقامي، واستقرّت حدوده عند حدود مقامات البديع(398ه) والحريري(516ه)، ولم يطعن في تلك الصّوى طاعن، فمثّلت طريقتهما نهجاً وقواعد خطا الأندلسيون على هداها، وصارت محاكاتهما إبداعاً، فتنامى التّقليد المصنوع إيحاءً بالاقتداء؛ الذي كان بذاته دليلاً على التفوّق.ولا يكاد يتفق للباحثين رأي حول طبيعة العمل القصصي في المقامات وقيمته الفنية، فمنهم من رفض وجوده رفضاً تاماً، ومنهم من يؤكد وجوده بإصرار، ونرى أن أحكام المعارضين والمثبتين قد جنحت إلى التعميم، فالمقامة جنس أدبي قائم بذاته، له خصائصه الفنية الخاصة به وإن تداخلت حدوده مع فنون أدبية أخرى. وقد حُدَّت المقامة بأنها سرد قصصي حواري فَكِه، يرويه بطل حاذق يخفي شخصيته بما يلائم المقام والمناسبة، ويلجأ إلى الحيل للتخفيف من متاعب الحياة، ويبرع في التخلص من المآزق وفي التماس العيش بطرق ملتوية.The Maqamat art grew up and its limits settled down at Al Badeea Maqamat limits(398 AH), and Al Hariri (516 AH). No one contested that. Thus, their methods represented rules and concept which the Andalusian followed. And their imitation became creation and the manufactured imitation increased suggesting the following of the patterns which were themselves an evidence of superiority. Researchers, almost, haven’t got one opinion about the nature of the narration in the Maqamat and its artistic value. Some of them refused it completely: others confirmed it permanently. We notice that the judgement of the opposers and the confirmers tended to generalization. The Maqama is a literary genre which has its own artistic qualities even though its limits interacted with other literary arts. The essay has its importance because it aims at conceiving the Andalusian Maqama limit, and the narrative elements in it, depending on inducting some of the Andalusian Maqama describing and analyzing it.